Experimental work organization on the methodology use of psychic readiness formation to overcoming competitive obstacles and difficulties - Kamalieva, G. A. (The Russian Journal of Physical Education and Sport, 2017)
Annotation. In terms of the changing relations in the sphere of physical culture and sports it is very difficult to overcome difficulties and obstacles, which appear during sportsmen`s competitive activity. Material. The article reveals the essence of experimental work on the methodology use, specially created for this situation. Great attention is paid to experimental substantiation of competitive difficulties and obstacles overcoming methodology, which appear in sports activity of volleyball players. Research methods: scientific and scientific-methodical literature analysis and summarizing, pedagogical testing, judgemental method, psychodiagnostics, pedagogical experiment, methods of mathematical statistics. Results. The methodology is created of psychic readiness formation among volleyball players to overcome competitive obstacles and difficulties. Experimental work on the methodology check was held in three stages on the basis of volleyball federation of Almetyevsk (Russia). For this purpose the experimental group and the control group were created. In the experimental group methodology was used taking into consideration the needs, revealed during the survey. In the control group teaching was according to a standard form. Summarizing the results of the pedagogical experiment we can say, that the experimental methodology use leads to considerable quickness increase of making tactical decisions, psycho-emotional state optimization in terms of unexpected competitive obstacles and difficulties, effectiveness of competitive activity increase. Conclusion. Created by us methodology of psychic readiness formation among sportsmen provides the level of special knowledge, skills, affective tolerance to difficulties and intellectual abilities of sportsmen increase, such as the ability to percept, attention focusing, cogitative material operation, memory, logical thinking, quickness of making decisions.